The Non-Canonical Role of Aurora-A in DNA Replication - Tsunematsu, Takaaki; Arakaki, Rieko; Yamada, Akiko; Ishimaru, Naozumi; Kudo, Yasusei (Frontiers in Oncology, 2015)
Aurora-A is a well-known mitotic kinase that regulates mitotic entry, spindle formation, and chromosome maturation as a canonical role. During mitosis, Aurora-A protein is stabilized by its phosphorylation at Ser51 via blocking anaphase promoting complex/cyclosome (APC/C)-mediated proteolysis. Importantly, overexpression and/or hyperactivation of Aurora-A is involved in tumorigenesis via aneuploidy and genomic instability. Recently, the novel function of Aurora-A for DNA replication has been revealed. In mammalian cells, DNA replication is strictly regulated for preventing over-replication. Pre-replication complex (pre-RC) formation is required for DNA replication as an initiation step occurring at the origin of replication. The timing of pre-RC formation depends on the protein level of geminin, which is controlled by the ubiquitin–proteasome pathway. Aurora-A phosphorylates geminin to prevent its ubiquitin-mediated proteolysis at the mitotic phase to ensure proper pre-RC formation and ensuing DNA replication. In this review, we introduce the novel non-canonical role of Aurora-A in DNA replication.